2023
DOI: 10.3390/rs15041072
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for High-Resolution Mapping of Soil Organic Matter (SOM) by the Integration of Fourier Mid-Infrared Attenuation Total Reflectance Spectroscopy (FTIR-ATR), Sentinel-2 Images, and DEM Derivatives

Abstract: Soil organic matter (SOM), as the greatest carbon storage in the terrestrial environment, is inextricably related to the global carbon cycle and global climate change. Accurate estimation and mapping of SOM content are crucial for guiding agricultural output and management, as well as controlling the climate issue. Traditional chemical analysis is unable to satisfy the dynamic estimation of SOM due to its low timeliness. Remote and proximal sensing have significant advantages in terms of ease of use, estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…The study assessed the predictive capabilities of various ML models and found that a hybrid method combining the Cubist model and the Bat algorithm yielded the best results with an R 2 value of 0.63. To improve the accuracy, Xu et al 99 combined a hand-held FTIR (Agilent 4300) with satellite NIR data for SOC analysis. They compared the prediction performance of different machine learning models: PLS, CNN, and SVM.…”
Section: Midinfrared (Mid-ir) Fourier-transformed Infrared (Ftir)mentioning
confidence: 99%
“…The study assessed the predictive capabilities of various ML models and found that a hybrid method combining the Cubist model and the Bat algorithm yielded the best results with an R 2 value of 0.63. To improve the accuracy, Xu et al 99 combined a hand-held FTIR (Agilent 4300) with satellite NIR data for SOC analysis. They compared the prediction performance of different machine learning models: PLS, CNN, and SVM.…”
Section: Midinfrared (Mid-ir) Fourier-transformed Infrared (Ftir)mentioning
confidence: 99%
“…The loss of carbon further intensifies the greenhouse effect by increasing the temperature, resulting in lower soil moisture and so promoting further carbon losses [54]. Changes in SOC are an essential indicator for the loss of nutrients from black soils and for soil response to the greenhouse effect [55,56].…”
Section: Loss Characteristics and Influencing Factors For Organic Car...mentioning
confidence: 99%
“…Obtaining useful information about the mineralogical composition of the soil as well as the content and character of organic matter in laboratory conditions has a significant impact on expanding the possibilities of remote sensing methods. 45 ASTER has seven spectral bands in the shortwave IR region and five in the MIR region. For the calibration of these satellites, it is necessary to obtain as much information as possible in idealized laboratory conditions.…”
Section: Comparative Evaluationmentioning
confidence: 99%